Plant communities along the international coastal highway of Nile delta, Egypt - El-Amier, Yasser A.; Abd El-Gawad, Ahmed M. (Journal of Scientific Agriculture, 2017)
The construction of highways promotes several changes in the roadside habitat, vegetation, and plant invasion. The present study aimed to describe the plant communities-environment interactions of the international coastal highway from Port-Said to Abu-Qir, northern Nile delta coast of Egypt. A total of 146 species (83 annuals, 4 biennials, and 59 perennials), belonging to 116 genera and 33 families were recorded in 80 stands. The Mediterranean chorotype is the most represented. The cluster analysis of stands yielded four communities. The community I was dominated by Silybum mariannum, community II was dominated by Mesembryanthemum crystalinum, Community III is the largest one and was co-dominated by Hordeum murinum and Senecio glaucus and community IV was co-dominated by Cakile maritima and S. glaucus. Diversity indices showed more richness of communities II and more evenness of community IV. Electric conductivity, porosity, soil texture, Na+, Cl- and bicarbonate showed significant variation among communities. The soil of C. maritima and S. glaucus community was more saline (1.78 ms cm-1). The application of CCA showed that communities II and III were mainly correlated with salinity and organic matter. The present study revealed that roadside habitat of the international coastal highway dominated by different plant communities which correlated with the habitat structure, salinity, and anthropogenic activities. Furthermore, nine invasive species were recorded in this study which could be attributed to the increment of human activities after the construction of the highway.